Landscape geomorphic characteristic impacts on greenhouse gas fluxes in exposed stream and riparian sediments. Issue 7 (16th June 2016) - Vidon, Philippe; Serchan, Satish
Abstract : In forest streams, riparian zone gas emissions exceed those of in-stream locations, with most CO2eq driven by CH4 production. Abstract : While excessive releases of greenhouse gases (GHG: N2 O, CO2, CH4 ) to the atmosphere due to the burning of fossil fuel remains a concern, we also need to better quantify GHG emissions from natural systems. This study investigates GHG fluxes at the soil–atmosphere interface in a series of 7 stream reaches (riparian zones + exposed streambed sediment) across a range of geomorphic locations from headwaters reaches to lowland wetland reaches. When riparian fluxes (RZ) are compared to fluxes from in-stream locations (IS) under summer baseflow conditions, total CO2 -equivalent (CO2eq ) emissions are approximately 5 times higher at RZ locations than at IS locations, with most CO2eq driven by CH4 production at RZ locations where wet conditions dominate (headwater wetlands, lowland wetlands). On a gas-by-gas basis, no clear differences in N2 O fluxes between RZ and IS locations were observed regardless of locations (headwater vs. lowland reaches), while CO2 fluxes were significantly larger at RZ locations than IS locations. Methane fluxes were significantly higher in wetland-influenced reaches than other reaches for both RZ and IS locations. However, GHG fluxes were not consistently correlated to DOC, DO, NO3 −, NH4 +, or water temperature, stressing the limitations of using water quality parameters to predict GHG emissions at the floodplain scale, at least during summer baseflow conditions. As strategies are developed to further constrain GHG emission for whole watersheds, we propose that approaches linking landscape geomorphic characteristics to GHG fluxes at the soil–atmosphere interface offer a promising avenue to successfully predict GHG emissions in floodplains at the watershed scale.